Modern Nomad and Colonialism - Mickūnas, Algis (Sociologija. Mintis ir veiksmas, 1999)
The aim of the article is to discuss the distinction between the East and the West or Orient and Occident and the importance of geographical demarcations for the civilizational analysis. The author notes the cultural grounds of the distinction and questions its uses to understand and the democratic modes of life on the hand and despotic on the other. The author develops the analysis of the liberalizing and constraining aspects of modes of life by discussing the role of the everyday discourse, imagination, mass media, arts and aesthetic taste in the formation of the stratified societal relations.